Forest strips increase connectivity and modify forests functioning in a deforestation hotspot - Camba Sans, Gonzalo Hernán; Veron, Santiago Ramón; Paruelo, José María (Elsevier, 2021)
Land use changes are occurring with unprecedented magnitude and intensity, imposing global impacts on ecosystem services (ES) and biodiversity. While the impacts of land use changes are increasingly recognized, understanding how landscape connectivity is related to ecosystem functioning is lacking. In the Argentinian Dry Chaco, deforestation increased forest fragmentation but strips of native forest (linear remnants) were usually left after clearings. Although the number of ecological studies on forest strips has increased, their contribution to forest connectivity and functioning has not been assessed. We evaluated the contribution of forest strips to forest connectivity and estimated its effect on forests’ functioning considering low, moderate, and high species’ dispersal abilities in our estimation. The effects of forest strip connectivity contribution to the forests’ Ecosystem Services Supply Index (Forests’ ESSI) was also analyzed. Forest strips contributed on average 6% and up to 40% to forest connectivity for moderate dispersal abilities, while low and high dispersals presented low values in almost all cases. The connectivity contribution was highest (between 15 and 40%) and variable for moderate dispersal abilities in landscapes with between 25 and 35% of forest cover. High connectivity contribution was generally achieved for low and moderate dispersals when forest strips conformed a network among forest patches. Forest strip connectivity significantly increased the forests’ ESSI (between 1.3 and 2.4% per unit of connectivity contribution) and its effect was higher in comparison to forest amount and fragmentation. This study provides insights for planning the location of forest strips and forest remnants in agricultural landscapes, thus increasing forest connectivity for enhancing ecosystem functioning.